Exploring the dynamics of seasonal surface features using coastal and regional ocean community model - D. Jaishree; P.T. Ravichandran; D.V. Thattai (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Studying the monthly variations in the surface features of the Bay of Bengal is a complex task that involves numerous large-scale ocean-atmosphere dynamics. This study identified the bay’s changing circulation patterns over recent decades as a crucial study area requiring in-depth research. Understanding the changes in circulation patterns provides valuable insights into the Bay dynamics. It helps identify the potential impacts of climate change, ocean currents, and other factors on the bay’s ecosystem. This study aims to understand the seasonal variability of the Bay of Bengal’s surface circulation features using a high-resolution numerical Coastal and Regional Ocean Community simulations model. METHODS: To conduct the study in the Bay of Bengal, the Coastal and Regional Ocean Community model, a numerical ocean model, was utilized. The high-resolution numerical model for ocean circulation is three-dimensional and uses hydrostatic primitive equations in generalized curvilinear coordinates. Simulations were conducted over 8 years using a grid comprising 256 x 249 horizontal surface points to model a range of ocean-atmospheric parameters. This grid provided an approximate resolution of 10 kilometers.FINDINGS: The findings are based on the model’s enhanced performance compared to previous study results. It was observed that the sea surface temperature remains above 28 degrees Celsius throughout the bay except in winter. During the monsoon season, surface salinity was observed to be reduced in the Bay of Bengal’s northern region and western and eastern boundaries. Surface eddies along the western bay extend to deep waters before the onset of monsoon. The net heat flux in the bay has been determined as positive before monsoon, negative post-monsoon, and mixed during the monsoon season.CONCLUSION: This analysis focuses on the ocean surface layer with more prominent dynamics. Various surface parameters were calculated, and discussions on surface temperature, salinity, D20, D26, and net heat flux across seasons have been presented.